Geographic disparities in bladder cancer incidence among men in the department of Bouches-du-Rhône. (13th November 2019) - Mantey, K; Cortaredona, S; Grisoni, V; De Fromont, M; Albert, P; Karsenty, G; Pascal, L
Abstract: : Bladder cancer incidence is investigated in the department of Bouches-du-Rhône to provide answers to the population reporting an excess of cancer cases in industrial areas. The study aimed to describe the geographical variations of bladder cancer incidence among men and detect potential spatial clusters without point source specification. Incident cases diagnosed between 2013 and 2016 were extracted from the departmental observatory of cancers REVELA13. Age-standardized incidence ratios (SIRs) were calculated for each commune and bayesian smoothed risk estimate based on the Besag, York and Mollie model were computed for incidence mapping. Morans'I, Potthoff-Whittinghill and Tango statistic tests were used to investigate global clustering and the spatial scan statistic of Kulldorf (SaTScan) was used to investigate local clustering. Analyses were adjusted on a French deprivation index, access to health-care services and population density. During the study period, 1 735 cases of bladder cancers were diagnosed among men. The study found a spatial heterogeneity (p < 0.01) and aggregation (p < 0.01) but no spatial autocorrelation (p = 0.09). Bayesian smoothed SIRs were not related to the confounding factors studied. An over-incidence was observed in the communes located in the South East of the department including Marseille, the biggest city of the study area. SaTScan algorithms detected two significant high-risk clusters in the same area (RR = 1.50 and 1.38). Introduction of each confounding factors in spatial scan detection, changed slightly the shape of clusters and/or the value of the relative risk but not the location. None high-risk cluster was detected in the communes of the industrial area. Spatial analysis provides a first answer to the population concerning an excess of risk of bladder cancer at commune level. However, more analysis should be led to identify etiological factors or common environmental exposure. Key messages: Geographic disparities exist in bladder cancer incidence among men at a commune level in the department of Bouches-du-Rhône. Spatial analysis show excess of risk of bladder cancer in the south-east of the department including the urban area of Marseille.